Hematopoietic Stem Cell Transplantation From Haploidentical Donors in Aplasia After Cladribine/Cytarabine Chemotherapy for Refractory Acute Myeloid Leukemia or Myelodysplastic Syndrome - Vydra, Jan; Válková, Veronika; Čemusová, Barbora; Kolář, Michal; Nováková, Ludmila; Soukup, Petr; Šálek, Cyril; Vraná, Milena; Pytlík, Robert; Lesný, Petr; Vítek, Antonín; Cetkovský, Petr; et al. (Clinical lymphoma, myeloma & leukemia, 2019)
INTRODUCTION: Survival rate of patients with chemorefractory acute myeloid leukemia (AML) or myelodysplastic syndrome with excess blasts (MDS-EB) is poor. Allogeneic hematopoietic cell transplantation (HCT) is the only potentially curative therapy in these patients. PATIENTS AND METHODS: We report a retrospective analysis of outcomes of therapy of 24 patients with AML or MDS-EB refractory to high-dose salvage chemotherapy or who had failed previous HCT, who received T-cell-replete HLA haploidentical HCT in aplasia after cladribine/cytarabine-based chemotherapy followed by reduced intensity or myeloablative conditioning. All patients had active disease before commencement of the treatment. RESULTS: Of the patients, 91.7% achieved complete remission (CR), whereas 2 patients (8.2%) died in aplasia. One-year relapse rate was 49.3%. Cumulative incidence of nonrelapse mortality (NRM) was 25.6%. In a subgroup of patients with HCT-comorbidity index score ≤ 3, NRM was 15.4%. Two-year overall survival and relapse-free survival were 30.6% and 22.6%, respectively. Incidence of grade 3 and 4 acute graft versus host disease was 21.3% and 8.3, respectively. CONCLUSION: We found that sequential therapy with HCT in aplasia after cladribine/cytarabine chemotherapy is feasible, results in high CR rates, and has acceptable toxicity profile; however, posttransplant relapse is common in patients treated with active disease.
Keywords: recidiva; Leukemia, Myeloid, Acute; kombinovaná terapie; transplantace hematopoetických kmenových buněk; Humans; Transplantation, Haploidentical; lidé středního věku; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Female; Aged; příprava pacienta k transplantaci; dospělí; protokoly protinádorové kombinované chemoterapie; mladý dospělý; senioři; lidé; myelodysplastické syndromy; haploidentická transplantace; Adult; ženské pohlaví; Male; Middle Aged; nemoc štěpu proti hostiteli; Retrospective Studies; incidence; Antineoplastic Combined Chemotherapy Protocols; Incidence; Transplantation Conditioning; Recurrence; Young Adult; retrospektivní studie; Myelodysplastic Syndromes; Combined Modality Therapy; mužské pohlaví; akutní myeloidní leukemie